Facial Rejuvenation in Indonesian Skin With a Picosecond 755-nm Laser - Wardhani, Putri Hendria; Prakoeswa, Cita Rosita Sigit; Listiawan, Muhammad Yulianto (Journal of Lasers in Medical Sciences, 2022)
Background: Skin aging is a natural process that occurs as people age, affected by various factors, ultraviolet irradiation is a major factor, leading to appear wrinkles, pigmentations, and textural irregularities. Laser had gained popularity for facial rejuvenation in the Asian population, but melanin rick skin type like Asian are more susceptible to pigmentary alterations. Majority of Indonesians have brown skin color and the rest have lighter skin color. The aim of this study is to know the efficacy and safety of the picosecond 755 nm laser on facial rejuvenation in Indonesian skin. Methods: This is a retrospective analysis of 20 healthy subjects with Fitzpatrick skin type III-V presenting with facial photoaging from 36 to 55 years old. Assessments were conducted at the baseline and 4 weeks after the second session of the treatment. Standardized photographs were taken from the front and side of both cheeks using VISIA. Clinical improvement was categorized as mild - excellent. Patients were also asked and examined about the presence of adverse events. Results: Patients were predominantly female with a mean age of 44 years old. Sixty percent of patients had a good improvement and 40% of patients had a moderate improvement. The VISIA analysis showed significant improvement in wrinkles, pigments, and textures (p < 0.001). Only mild anticipated adverse events were observed, and there was no post-inflammatory hyperpigmentation or hypopigmentation. Conclusion: Picosecond 755 nm laser is effective and safe for facial rejuvenation in Indonesian skin without significant adverse events.